When Control Backfires: The Double-Edged Role of Management Control Systems in Environmental Capabilities and Environmental Management Accounting Practices - Nilam Kemala Odang; Indah Murni; Khusnul Afifah Zharaura; Yongky Teguh Setiaji (Jurnal Dinamika Akuntansi dan Bisnis)
This study examined how environmental management control systems (EMCS) moderate the relationship between environmental capabilities (EC) and the implementation of environmental management accounting (EMA). By integrating EC and EMCS within a unified framework, the analysis draws on data from 900 non-financial Southeast Asian companies reporting ESG metrics from 2019 to 2023. Using ordinal logistic regression, the findings reveal that while EC positively influences EMA implementation, EMCS unexpectedly weakens this effect. This suggests that rigid or misaligned control systems may hinder the effective utilization of environmental capabilities. The study underscores the conditional role of EMCS and highlights the importance of contextually adaptive systems that support, rather than constrain, strategic environmental initiatives. It contributes to the literature by demonstrating how the EC–EMCS interaction can either facilitate or obstruct EMA implementation, particularly within the Southeast Asian context.